Orientation Singularity Analysis of Parallel Manipulators - Qimin Xu (IAES International Journal of Robotics and Automation (IJRA), 2016)
In this paper, an approach for orientation singularity analysis of parallel manipulators (PMs) is proposed by introducing several performance indices referred to theunique form of screw based Jacobian in the velocity transmission as well as force transmission. Here, to prove the effectiveness of the approach, an example of 3 degrees of freedom (DOF) prismatic-revolute-spherical (PRS) parallel manipulator (PM) is first presented to illustrate the fact that the distributions of singularity boundary of the proposed approach is consistence with the result referred to nonredunant PMs by Liu et al. [22]. Further, the proposed approach is an appropriate one not only for nonredunant PMs, but also for a class of redunant PMs by providing another example of the redunant variable geometry truss (VGT) PM, since the performance index of orientation singularity for the manipulator can becreated only by determining the unique form of screw based Jacobian.